From innovation to implementation: viability of the increased use of insects as food and feed - Dobermann, Darja (2019)
As global pressures on food systems mount the push for novel solutions, particularly how to source new forms of protein, has intensified. One possible solution, which has garnered attention in recent years, is increasing the use of edible insects as food and feed. Preliminary research has suggested that increasing the use of insects could be beneficial as they require less water, land and feed to rear and thus have a smaller environmental footprint than does any other protein source, whilst also maintaining high nutritional quality. Furthermore, insects have high micronutrient levels and could therefore play a vital role in alleviating many forms of malnutrition. Considering insects as a source of food and feed is not far-fetched as there are more than 2000 documented edible species and 2 billion people globally already regularly consume insects. However, reliable data to substantiate the claims made about the potential of sustainable implementation of insects within food systems are lacking. This thesis starts with a review (Paper I) of the current opportunities and major hurdles facing the incorporation of edible insects into existing dietary systems. From this It is apparent that whilst there are environmental and nutritional opportunities these are presently hampered by a lack of information on how to adequately rear and process insects. There is also limited data available on the safety of incorporating insects into the diets of animals, including humans, which have not traditionally consumed them. Papers II and III of this thesis examine key aspects of how to rear insects and what diets would ensure that they would be socially, economically and environmentally sustainable. It has been frequently stated that insects can be farmed easily on bio-waste sources so two trials were done to test products of various composition as feed for Gryllus bimaculatus and Hermetia illucens, two species commonly used as food or feed. The trial with H. illucens showed that the larvae easily survived and thrived on a brewing waste from Uganda, suggesting that this is a viable option. However, a second trial with G. bimaculatus showed that they could not achieve adequate survival rates when fed on food waste, beer brewing waste or cow manure and the only way to improve this was to introduce a high quality, non-waste, feed for at least 1 week prior to being switched to a waste food source. Thus, limiting the sustainability of the system. As well as considering the production of insects for food, it was also important to look at the nutritional quality and Paper IV examines the effects of heat-processing on the nutritional content of G. bimaculatus. This showed a significant effect of drying temperature on the lipid profile of G. bimaculatus; crickets that had been freeze-dried containing significantly more polyunsaturated and total fatty acids than those dried at 120℃. One way of gaining a wide acceptance of insects in the food chain is to use them to rear fish for human consumption. Thus, Paper V reports trials where two meals were created using either H. illucens larvae or G. bimaculatus. These were analysed for their nutritional content, showing that both met or exceeded the basic nutritional requirements for omnivorous fish. A fish-feeding trial was then conducted with Nila tilapia, whereby the fish were fed on either a fish-meal, plant-based, H. illucens-based, or G. bimaculatus-based diet for 12 weeks, over which feed consumption, growth and survival were monitored. This demonstrated that the insect-based diets were just as good as the others supporting the view that insects as fish feed are a promising sustainable protein source. It is evident from the findings presented in this thesis that the use of insects as food and feed is a complex issue that needs to be considered carefully. There are benefits to insects in the form of their favourable nutritional profile and in the success of using them as an omnivorous fish feed component in place of fish-meal. However, it is equally evident that a key area requires significant further exploration. If the rearing of insects is to be sustainable they need to be able to use a sustainable food source such as bio-waste and this will need further optimisation to ensure that it produces the same results as the chicken feed alternative that is being used currently. It will also have to be compatible with the downstream use of the insects interms of geographic location and cultural considerations.